Aberration of Mind Suicide and Suffering in the Civil War-Era South - Sommerville, Diane Miller (University of North Carolina Press, 2018)
More than 150 years after its end, we still struggle to understand the full extent of the human toll of the Civil War and the psychological crisis it created. In Aberration of Mind, Diane Miller Sommerville offers the first book-length treatment of suicide in the South during the Civil War era, giving us insight into both white and black communities, Confederate soldiers and their families, as well as the enslaved and newly freed. With a thorough examination of the dynamics of both racial and gendered dimensions of psychological distress, Sommerville reveals how the suffering experienced by Southerners living in a war zone generated trauma that, in extreme cases, led some Southerners to contemplate or act on suicidal thoughts. Sommerville recovers previously hidden stories of individuals exhibiting suicidal activity or aberrant psychological behavior she links to the war and its aftermath. This work adds crucial nuance to our understanding of how personal suffering shaped the way southerners viewed themselves in the Civil War era and underscores the full human costs of war.